Characteristics of the Psidium cattleianum invasion of secondary rainforests. (1st October 2015) - Tng, David Y. P.; Goosem, Miriam W.; Paz, Claudia P.; Preece, Noel D.; Goosem, Stephen; Fensham, Roderick J.; Laurance, Susan G. W.
Abstract: Strawberry guava ( P sidium cattleianum ) is a shade‐tolerant shrub or small tree invader in tropical and subtropical regions and is considered among the world's top 100 worst invasive species. Studies from affected regions report deleterious effects of strawberry guava invasion on native vegetation. Here we examine the life history demographics and environmental determinants of strawberry guava invasions to inform effective weed management in affected rainforest regions. We surveyed the vegetation of 8 mature rainforest and 33 successional sites at various stages of regeneration in the Australian Wet Tropics and found that strawberry guava invasion was largely restricted to successional forests. Strawberry guava exhibited high stem and seedling densities, represented approximately 8% of all individual stems recorded and 20% of all seedlings recorded. The species also had the highest basal area among all the non‐native woody species measured. We compared environmental and community level effects between strawberry guava‐invaded and non‐invaded sites, and modelled how the species basal area and recruitment patterns respond to these effects. Invaded sites differed from non‐invaded sites in several environmental features such as aspect, distance from intact forest blocks, as well as supported higher grass and herb stem densities. Our analysis showed that invasion is currently ongoing in secondary forests, and also that strawberry guava is able to establish and persist under closed canopies. If left unchecked, strawberry guava invasion will have deleterious consequences for native regenerating forest in the Australian Wet Tropics.